Single-step production of sustainable aviation fuel by deoxygenation and isomerization of palm kernel oil using Pt-, Pd-, or Ru-incorporated Re/SAPO-11 catalysts - Wanichaya Praikaew; Jirawat Chuseang; Vorranutch Itthibenchapong; Sakhon Ratchahat; Weerawut Chaiwat; Wanida Koo-amornpattana; Chularat Sakdaronnarong; Apiluck Eiad‐ua; Suttichai Assabumrungrat; Atthapon Srifa (Journal of Analytical and Applied Pyrolysis, 2025)
The production of sustainable aviation fuel (SAF) from agricultural bioresources is recognized as a sustainable biorefinery application that aligns with the United Nations Sustainable Development Goal 7 (Affordable and clean energy). Herein, bimetallic catalysts (Pt-Re, Pd-Re, and Ru-Re) supported on SAPO-11 were synthesized using a conventional impregnation method for single-step production of SAF through the deoxygenation and isomerization of palm kernel oil. These catalysts were compared with monometallic catalysts (Re, Pt, Pd, and Ru) as benchmarks. Interestingly, the incorporation of Pt, Pd, or Ru with Re/SAPO-11 markedly enhanced deoxygenation and isomerization activities, achieving nearly theoretical yields of 70 % for n- and iso-alkanes with 100 % triglycerides (TGs) conversion. Among the tested catalysts, the bimetallic Ru-Re catalyst produced the highest jet fuel yield of 60 % with a high iso-to-n-alkane (i/n) ratio of 1.2 under conditions of 360°C reaction temperature, H 2 pressure of 30 bar, weight hourly space velocity of 2 h −1 , and an H 2 /oil ratio of 1000 N(cm 3 /cm 3 ). Additionally, the bimetallic Ru-Re catalyst demonstrated excellent stability over 60 h of continuous operation, maintaining exceptional compositions of straight-chain and branched alkane products. The unrefined biofuel produced with the Ru-Re catalyst exhibited the lowest freezing point (T f ) at −31.9°C, as determined by differential scanning calorimetry, without the use of additive compounds. Furthermore, when blended with commercial Jet A at 10 % (v/v), the resulting jet fuel blend achieved a T f of ∼–60.1°C, meeting Jet A standards. • Pt, Pd, or Ru-Re/SAPO-11 were developed for SAF production from palm kernel oil. • Single-step production of SAF was gained by simultaneous deoxygenation and isomerization. • Highest jet yield comprising normal and iso alkanes was obtained using the RuRe/SAPO-11. • Bimetallic RuRe/SAPO-11demonstrated the excellent stability for 60 h of time-on-stream. • Tf of the blended jet fuel using RuRe/SAPO-11 was –60.1 °C in the range of Jet A standard.
Keywords: Catalysis and Hydrodesulfurization Studies; Biodiesel Production and Applications; Catalytic Processes in Materials Science